Centridini Bees as Manageable Pollinators of West Indian Cherry (Malpighia emarginata, Malpighiaceae) Orchards in Southeast Brazil - Diego Moure-Oliveira; Reinanda Lima; Morgana S. Sazan; Cláudia Inês Silva; Carlos A. Garófalo (Sociobiology)
The West Indian cherry (Malpighia emarginata), commonly referred to as “Acerola”, has attracted particular interest due to its high vitamin C content in the fruit. One of the limitations observed in Acerola crops is their dependence on cross-pollination, which is usually performed by Centris species. This study investigated the occupation of trap-nests in an Acerola orchard by bees of the genus Centris to identify species that could be indicated as providers of pollination services in these orchards. Centris analis and Centris tarsata, the species occupying the traps, displayed a seasonal pattern in their nesting activities, with the highest frequencies aligning with the peaks of the crop’s flowering. Both bees explored 48 plant species, with M. emarginata being the most important pollen source and floral oil, primarily for C. analis. The high preference observed in the diet of C. analis and the seasonal pattern in the nesting activity of C. tarsata indicate that both species are effective pollinators of M. emarginata crops.